Enhanced Bifunctional Catalytic Activity of Cobalt Phosphide Flowers Anchored N‐Doped Reduced Graphene Oxide for Hydrogen and Oxygen Evolution. Issue 15 (4th August 2020) - Veettil Vineesh, Thazhe; Vijayakumar Anagha, Usha; Purayil Dileep, Naduvile; Cheraparambil, Haritha; Nambeesan, Jyothish; Shaijumon, Manikoth M.
Abstract: In this work, we demonstrate morphology‐controlled synthesis of flower‐like cobalt phosphide decorated on nitrogen doped reduced graphene oxide (NrGO), which act as bifunctional electrocatalysts toward both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The as‐synthesized CoP‐NrGO, formed via hydrothermal reaction followed by gas‐solid reaction, attains an OER current density of 10 mA cm −2 at an overpotential of 0.38 V, which is on par with that of its Co(OH)2 ‐NrGO counterpart and the benchmarked IrO2 catalyst. On the other hand, the conversion of Co(OH)2 to CoP is seen to improve its HER performance drastically. CoP‐NrGO reached a current density of 10 mA cm −2 at an overpotential of 0.184 V which is 0.204 V anodic to Co(OH)2 ‐NrGO. The improved performance could be attributed to reduced charge transfer resistance following the phosphidation process. From the comparison of the electrocatalytic performance of the catalysts, it can be inferred that phosphidation has a considerable effect only on the cathodic HER. Abstract : Dual intentions : Morphology‐controlled synthesis of cobalt phosphide flowers decorated on nitrogen‐doped reduced graphene oxide (NrGO) is demonstrated as efficient bifunctional electrocatalysts for both hydrogen and oxygen evolution in alkaline medium. The high activity, high stability, and cost‐effectiveness make CoP‐NrGO a most promising electrocatalyst for overall water splitting.